TA effectiveness in Nigerian mixed ability classrooms: Finding the gap and closing it - Atiya, Karachi (2015)
The aim of this investigation was to determine how effective TAs were in relation to the increasing demands on them to play a more active role in supporting pupil’s learning in Nigerian mixed ability classrooms, finding if a gap existed and from the data, recommending ways of closing them. The area of TA practice has received quite a bit of attention recently, with the most recent DISS Project by Blatchford et al, being the largest study of its kind in this field. The findings were surprising as it was discovered that contrary to general belief, the deployment of TAs to support pupils did not always have a positive effect. In order to explore this phenomenon, four questions were asked. Firstly, what are the perceptions of TAs about their changing work roles in the classroom? Secondly, what kind of support do Nigerian teachers and school leaders presently require from TAs in mixed ability/inclusive classrooms? Thirdly, is there a gap between TA roles and competencies? Finally, in view of the emerging data, how can any identified gap be closed? It was important to locate this enquiry in the Nigerian context as there was very little available data in this area. This took on more significance when national policies were reviewed and which turned up some interesting facts and further justified the study. A qualitative method was employed in finding the answers, with questionnaires sent out to TAs, teachers, and school leaders. Also, interviews were conducted with two notable educational consultants. The resultant data proved that the TA’s role had evolved to include more direct pedagogical support to pupils and though the change is welcomed by the TAs, they required more support from the school, and more especially from the teacher to do so effectively. Though they were being trained along with the teachers, there was a disconnection between the training received and the application in practice. Motivation was low and the quality of the communication between teachers and TAs was an area that demanded attention. Gaps were identified and recommendations were made, taking into cognisance the local context and challenges and the international views on parallel issues.